IDENTIFICATION OF COMMUNICATION BETWEEN FAMILY AND PRESBYACUSIS PATIENT WHO STAYS IN ONE HOUSE - AHMAD IKHLASUL AMAL (Fakultas Ilmu Keperawatan Universitas Islam Sultan Agung, Semarang, 2017)
Presbyacusis hearing loss is common in elderly. Patients with presbyacusis may feel neglected by the family and the surrounding environment. It should be takes the right way to communicate with presbyacusis patients, so that communication can be done effectively. This study aims to identify the phenomenon of family communication with presbyacusis patients who stays in one house. Qualitiataive research design was used in this reserch with phenomenologycal approach. In-depth interviews and observation was used as data collection method. The results of the research found that the family have an understanding about the meaning of communication which is talking alone and talking with others. Family barriers when communicating with presbyacusis patients are difficult to understand what is the family talking about, difficult to talk, disconnected, family feel annoyed and must be patient when communicating. The family communicates with presbyacusis patients using verbal (verbal) communication such as repetition of speech, non-verbal communication (gesture) that is by mouth movement, touching the shoulders, face-to-face when communicating, hand movements. As a conclusion of this research was obtained the understanding of communication, family barriers when communicating with presbiakusis patients, the way families communicate, family reasons using verbal communication (verbal) and non-verbal (cues).Keywords: family communication, presbyacusis, phenomena